Effects of different curing methods and aggregate salt treatment on concrete freeze-thaw durability and how these methods can be used to accelerate KDOT aggregate qualification procedures - Armstrong, Cale (Kansas State University, 2016)
The Kansas Department of Transportation (KDOT) currently practices a six-month procedure for determining freeze-thaw durability of coarse aggregate intended for use in concrete pavement. In addition to the excessive amount of time required to conduct this procedure, the testing conditions fail to replicate the accelerated rate of concrete deterioration commonly caused by deicer salt exposure in freeze-thaw environments. An experimental study was conducted in an attempt to reduce the duration of this aggregate qualification procedure. Limestone course aggregates from different quarries were used to batch concrete specimens. These specimens were subjected to curing regimes of different durations before being exposed to repeated cycles of freezing and thawing. The effects of the curing methods on freeze-thaw durability were then investigated. Another segment of this study entailed the immersion of coarse aggregate in salt brine solution prior to concrete batching. Salt-treated and non-salt-treated specimens were subjected to two different methods of freeze-thaw cycling to determine if the presence of salt could differentiate between aggregates with high and low performance. This study found that shorter curing methods, along with adjusted performance requirements, could be used to develop a shorter aggregate qualification procedure. It also found that shorter periods of time in more severe freeze-thaw conditions produced comparable concrete durability results to those of the current test method. Salt treatment of aggregates could indicate a difference in performance of aggregates when exposed to salts in freeze-thaw conditions. It could also be useful in determining frost resistance of hardened cement paste.
Keywords: Aggregate; Curing; Salt; Concrete; Freeze; Thaw